2021
DOI: 10.1093/ndt/gfab170
|View full text |Cite
|
Sign up to set email alerts
|

Urgent-start dialysis in patients referred early to a nephrologist—the CKD-REIN prospective cohort study

Abstract: Background The lack of a well-designed prospective study of the determinants of urgent dialysis start led us to investigate its individual- and provider-related factors in patients seeing nephrologists. Methods CKD-REIN is a prospective cohort study that included 3033 patients with CKD (mean age, 67 years; 65% men; mean estimated glomerular filtration rate (eGFR), 32 mL/min/1.73 m2) from 40 nationally representative nephrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…In addition, the relationship between specialized management of patients with ESRD, emergent initiation of dialysis, and survival rate were confirmed. As we previously reported 17 , emergent initiation of dialysis is related to increased mortality [18][19][20] . Patients who undergo urgent initiation of dialysis often require rapid care and the poor general condition at that time of dialysis worsens the survival rate.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, the relationship between specialized management of patients with ESRD, emergent initiation of dialysis, and survival rate were confirmed. As we previously reported 17 , emergent initiation of dialysis is related to increased mortality [18][19][20] . Patients who undergo urgent initiation of dialysis often require rapid care and the poor general condition at that time of dialysis worsens the survival rate.…”
Section: Discussionmentioning
confidence: 73%
“…Factors such as polypharmacy, living alone, low health literacy, poor predialysis care, nonattendance at dialysis information sessions, surgical delays in vascular access, and lack of patient education programs 19 , 28 32 are considered risk factors for unplanned dialysis, and these factors could cause issues related to the unmeasured confounders of the emergent initiation of dialysis in this study. For example, Victor Fages et al reported that the adjusted odds ratios for urgent-start dialysis were 2.14 (1.47–4.57), 2.22 (1.28–3.84), and 2.14 (1.17–3.90) for polypharmacy, living alone, and low health literacy, respectively 19 . We recognize that these unmeasured confounders are a potential source of bias in our cohort study; therefore, future studies including these variables should be conducted to provide an accurate estimate.…”
Section: Discussionmentioning
confidence: 95%
“…To achieve fast and extensive vaccination in our Unit, according to the recommendations [ 8 ], we worked closely with the local Primary Healthcare providers and the local vaccination hub. The vaccine was administered intramuscularly in the deltoid muscle, on a dialysis day, at least 30 min either pre- or post-dialysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the Council of the ERA-EDTA, the ERA COVID-19 Database (ERACODA) and the EuDial Working Groups, have issued calls to action on the timely vaccination of patients on HD, highlighting the extremely high burden of COVID-19 infection in this patient population [ 7 , 8 ]. To date, however, no data have been published on the efficiency and safety of either the BNT162b2 or any other vaccine in patients on chronic HD, even more so it is not known how efficient the first vaccine dose is, especially in view of the rather prolonged interval between the two doses as administered currently in the UK We present herein the 8-week outcomes of the first dose of the BNT162b2 vaccine in 83 patients on chronic HD.…”
Section: Introductionmentioning
confidence: 99%
“…This issue can be a common problem in some countries around the world. Referring patients for evaluation at a low GFR threshold, when a possible requirement for kidney replacement therapy is close at hand, may not help to shift this tendency in a more favourable direction since other factors are associated with urgent-start dialysis [ 81 ]. Age-adapted referral criteria have been adopted by some countries, such as Sweden, regions and healthcare systems [ 18 , 82 ], but no prospective studies have compared models and outcomes.…”
Section: Special Global Perspectives On Referral Criteriamentioning
confidence: 99%